2019
DOI: 10.1080/19490976.2019.1674124
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of host bile acids by members of the gut microbiota

Abstract: Bile acid biotransformation is a collaborative effort by the host and the gut microbiome. Host hepatocytes synthesize primary bile acids from cholesterol. Once these host-derived primary bile acids enter the gastrointestinal tract, the gut microbiota chemically modify them into secondary bile acids. Interest into the gut-bile acid-host axis is expanding in diverse fields including gastroenterology, endocrinology, oncology, and infectious disease. This review aims to 1) describe the physiologic aspects of colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
312
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(321 citation statements)
references
References 118 publications
(252 reference statements)
3
312
0
6
Order By: Relevance
“…Indeed, our results indicated that HDCA supplementation significantly increased fecal secondary BAs (HDCA and THDCA + TUDCA) and decreased fecal primary BA (TCA). Numerous evidences have demonstrated that secondary BAs are more toxic than their primary counterparts, and may damage the gut and lead to diseases 7,27 . In addition, TUDCA has been reported to exert neutral effect on proliferation of human preadipocytes and adipocytes 42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, our results indicated that HDCA supplementation significantly increased fecal secondary BAs (HDCA and THDCA + TUDCA) and decreased fecal primary BA (TCA). Numerous evidences have demonstrated that secondary BAs are more toxic than their primary counterparts, and may damage the gut and lead to diseases 7,27 . In addition, TUDCA has been reported to exert neutral effect on proliferation of human preadipocytes and adipocytes 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relative abundance of FamilyXIIITCG‐001 , which belongs to order Clostridiales , was significantly increased ( P = .0054) after HDCA supplementation. The genus Clostridium is one of the intestinal bacteria which perform both BSH deconjugation and 7α‐dehydroxylation, 7,8 and plays an important role in the production of secondary BAs. Thus, FamilyXIIITCG‐001 might elicit the similar role to that of Clostridium and be involved in the generation of secondary BAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary bile acids, which form the vast majority of the bile acids in the colon, may also be passively reabsorbed and enter the entero-hepatic circulation. As a result of this extensive metabolism, the final bile salt pool is deeply influenced by the microbiota composition of the individual and more than 50 different secondary bile acids are found in feces [47,48]. Moreover, the bile acid pool is involved in the feedback mechanism of bile acid synthesis.…”
Section: Figurementioning
confidence: 99%
“…These substances may affect a myriad of signaling pathways that might directly influence metabolic dysfunction, and contribute to NAFLD development and progression. Importantly, gut microbiota can modulate BA metabolism contributing to diversification of host BA, thus regulating BA‐dependent pathways mediated by dedicated BA receptors, such as FXR and TGR5 . In addition, similar to ALD, early in the disease, individuals with NAFLD may show impaired BA secretion resulting in increased intracellular BA concentrations .…”
Section: Introductionmentioning
confidence: 99%